1989
DOI: 10.1093/ndt/4.10.883
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Iron Overload in the Increased Susceptibility of Haemodialysis Patients to Bacterial Infections. Beneficial Effects of Desferrioxamine

Abstract: Iron overload, which is a common complication in haemodialysis patients, is known to enhance bacterial growth and virulence, and to alter phagocytosis. We reviewed the data of 61 haemodialysed patients to clarify the clinical relevance of iron status to the risk of bacterial infection. Increased concentrations of serum ferritin were associated with a greater infection rate (P less than 0.0025), which was already true for ferritin values between 500 and 1000 micrograms/l (P less than 0.025). Furthermore, in 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 0 publications
1
35
2
Order By: Relevance
“…When serum ferritin is above 1,000 µg/l, rHuEPO reverses polymorphonuclear granulocytes dysfunction in iron-overloaded hemodialysis patients following transfusion [35]. Desferrioxamine has beneficial effects on infection susceptibility in iron-overloaded patients (serum ferritin 500–1,000 µg/l) [34]. These facts are in contrast with our data where the initial serum ferritin levels were lower in patients who subsequently developed bacteremia.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…When serum ferritin is above 1,000 µg/l, rHuEPO reverses polymorphonuclear granulocytes dysfunction in iron-overloaded hemodialysis patients following transfusion [35]. Desferrioxamine has beneficial effects on infection susceptibility in iron-overloaded patients (serum ferritin 500–1,000 µg/l) [34]. These facts are in contrast with our data where the initial serum ferritin levels were lower in patients who subsequently developed bacteremia.…”
Section: Discussioncontrasting
confidence: 81%
“…A high serum ferritin level is also known to be a significant risk factor for infection [2, 33, 34]. When serum ferritin is above 1,000 µg/l, rHuEPO reverses polymorphonuclear granulocytes dysfunction in iron-overloaded hemodialysis patients following transfusion [35].…”
Section: Discussionmentioning
confidence: 99%
“…In a second multicenter, prospective study, multivariate analyses showed that three parameters are significant independent risk factors for bacterial infection in dialysis patients: History of bacterial infection, type of vascular access, and serum ferritin level Ͼ500 g/L (84). These data confirmed earlier findings that iron overload is associated with infectious complication in patients with ESRD (85)(86)(87). More intensive dosing of iron (defined as Ͼ10 vials of 100 mg iron dextran during a 6-mo period) was associated with significantly elevated rates of hospitalization and death as compared with hemodialysis patients who received Ͻ10 vials of iron (88).…”
Section: Critical Evaluation Of the Risk Of Iron Administrationsupporting
confidence: 88%
“…Iron is also necessary for the proliferation of bacteria [142], and for this reason, the possibility of an association between iron administration and the proliferation of bacteria has been raised [143]. Although one study found no significant association between high serum ferritin levels and the incidence of infections [144], other studies have shown that the risk of infections and the incidence of sepsis and vascular access-related infections significantly increased in HD patients with serum ferritin levels >331 and >500 ng/mL [145][146][147]. A systematic review of the safety and efficacy of intravenous iron showed that intravenous iron administration was effective for improving anemia and avoiding transfusion but that it caused a significantly higher risk of infectious disease [133].…”
Section: Statement 3-2 *mentioning
confidence: 99%